The Effect of Profitability, Managerial Ownership, Gender Diversity, and Audit Quality on The Integrity of Financial Statements - Ruth Cahaya Tarigan; Rina Tjandrakirana2 (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2025)
This research explores the effect of profitability, managerial ownership, gender diversity, and audit quality on the integrity of financial statements in banking sector companies listed on the Indonesia Stock Exchange between 2019 and 2023. Data was collected using a purposive sampling method, resulting in a sample of 180 companies. The analysis was performed using multiple linear regression with the support of SPSS 27 software. The findings revealed that profitability has a positive effect on the integrity of financial statements, while managerial ownership negatively affects it. Additionally, gender diversity and audit quality were found to have no impact on financial statement integrity. However, when considered together, these four factors have a positive and significant influence on the integrity of financial statements